2008
DOI: 10.1523/jneurosci.4686-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Dysfunction in Amyloid Precursor Protein Transgenic Mice: Contribution of Soluble and Insoluble Amyloid-β Peptide, Partial Restoration via γ-Secretase Inhibition

Abstract: The contributing effect of cerebrovascular pathology in Alzheimer's disease (AD) has become increasingly appreciated. Recent evidence suggests that amyloid-␤ peptide (A␤), the same peptide found in neuritic plaques of AD, may play a role via its vasoactive properties. Several studies have examined young Tg2576 mice expressing mutant amyloid precursor protein (APP) and having elevated levels of soluble A␤ but no cerebral amyloid angiopathy (CAA). These studies suggest but do not prove that soluble A␤ can signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
131
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 53 publications
25
131
0
Order By: Relevance
“…We have shown similar CV deficits in young Tg2576 mice (13). Moreover, we provided the most direct evidence to date that endogenous soluble Aβ plays a causal role in these CV deficits when we found that depletion of soluble Aβ via γ-secretase inhibition restores CV function in young Tg2576 mice (13).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…We have shown similar CV deficits in young Tg2576 mice (13). Moreover, we provided the most direct evidence to date that endogenous soluble Aβ plays a causal role in these CV deficits when we found that depletion of soluble Aβ via γ-secretase inhibition restores CV function in young Tg2576 mice (13).…”
supporting
confidence: 61%
“…For example, Iadecola and coworkers have shown that young APP transgenic mice (Tg2576) exposed to elevated levels of Aβ 40 and Aβ 42 (but no CAA) have reduced baseline cerebral blood flow (CBF) and decreased CBF responses to topical vasodilators (23,24,26). We have shown similar CV deficits in young Tg2576 mice (13). Moreover, we provided the most direct evidence to date that endogenous soluble Aβ plays a causal role in these CV deficits when we found that depletion of soluble Aβ via γ-secretase inhibition restores CV function in young Tg2576 mice (13).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…15,57,83,84 Support for this notion comes from experimental studies in mouse models of CAA, demonstrating decreased vascular reactivity in response to physiologic or pharmacologic stimuli compared with wild-type mice. 83,[85][86][87] Furthermore, mice with CAA showed increased susceptibility to induced ischemia, reflected by lower cerebral blood flow and increased infarct volume after middle cerebral artery occlusion. 83 It is not clear how well these animal models translate to the human disease, but the finding of impaired vascular reactivity in CAA is consistent with patient studies using functional transcranial Doppler 88 and functional MRI (fMRI).…”
Section: Pathophysiologic Mechanisms Of Ischemia In Cerebral Amyloidmentioning
confidence: 99%
“…After this stage, both endotheliumdependent and -independent responses are impaired. Hence, Ab-directed therapy to deplete soluble Ab only partly restores function, suggesting irreversible CAA-induced damage (Han et al, 2008). However, the prevailing view of soluble Ab vasoactivity has been challenged by studies showing the absence of cerebrovascular deficits after Ab superfusion (Hu et al, 2008).…”
Section: Transgenic Mouse Modelsmentioning
confidence: 99%